2012
DOI: 10.1002/ptr.4752
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Venezuelan Medicinal Plant Extracts for Cytostatic and Cytotoxic Activity Against Tumor Cell Lines

Abstract: There are estimated to be more than 20,000 species of plants in Venezuela, of which more than 1500 are used for medicinal purposes by indigenous and local communities. Only a relatively small proportion of these have been evaluated in terms of their potential as antitumor agents. In this study, we screened 308 extracts from 102 species for cytostatic and cytotoxic activity against a panel of six tumor cell lines using a 24-h sulphorhodamine B assay. Extracts from Clavija lancifolia, Hamelia patens, Piper san-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…[117] Similarly, di-(2-ethylhexyl) phthalate (DEHP) isolated from C. procera showed anti-tumor activity, [118] while Copper nanoparticles synthesised by using aqueous extract of C. procera latex showed cytotoxic [115] and cytostatic activity against tumor cells and cell lines. [119] Similarly, latex proteins from C. procera showed in vitro cytotoxicity [120] to human cancer cell lines and show in vivo growth inhibition of sarcoma 180. [121] It also showed anticancer and cytotoxic properties against hepatocellular carcinoma in a transgenic mouse model.…”
Section: Wound Healing and Hepatoprotectivementioning
confidence: 97%
“…[117] Similarly, di-(2-ethylhexyl) phthalate (DEHP) isolated from C. procera showed anti-tumor activity, [118] while Copper nanoparticles synthesised by using aqueous extract of C. procera latex showed cytotoxic [115] and cytostatic activity against tumor cells and cell lines. [119] Similarly, latex proteins from C. procera showed in vitro cytotoxicity [120] to human cancer cell lines and show in vivo growth inhibition of sarcoma 180. [121] It also showed anticancer and cytotoxic properties against hepatocellular carcinoma in a transgenic mouse model.…”
Section: Wound Healing and Hepatoprotectivementioning
confidence: 97%
“…This plant is widely used as traditional remedy for several diseases such as intestinal parasites [3], amenorrhea, high blood pressure [15], abdominal pain, convulsion, cataract, conjunctivitis [16] and treatment cancer in Peru [17]. The chemical components of H. indicum included flavonoids, terpenoids, glycosides, steroids, saponins, tannins, pyrrolizidine alkaloid and phenolic compounds related to anti-glaucomas [14], anthelmintic [18], anti-inflammatory, rheumatism, anti-tumor [19], antileishmanial, hemolytic and toxicological activities [9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is possible that the lack of antibacterial activity against these bacteria is due to a lack of diffusivity of the extract. In this context, it is proposed that this variation may be justified by the chemical composition of the samples, since higher molecular weight molecules tend to be more soluble and dispersible in liquid medium than in solid medium (Valgas et al, 2007).…”
Section: Results and Discussion Antibacterial Activity Of Protium Hebmentioning
confidence: 99%
“…Based on the ethnomedicinal use, it was found that ethyl ether extract of the resin of Protium kleinii showed excellent results its potent anti-inflammatory activity in topical use (Otuki et al, 2005). Pharmacologic studies with triterpenes α and β-amyrin isolated from extracts of the leaves and resin of species P. heptaphyllum demonstrated analgesic (Holanda Pinto et al, 2008), anti-inflammatory (Susunaga et al, 2001), antidepressant (Aragão et al, 2006), gastroprotective (Oliveira and Amaral, 2004) and cytotoxic (Taylor et al, 2012) activities. Another study with P. glabrescens resin demonstrated potent antimalarial activity for the species (Deharo et al, 2001).…”
Section: Introductionmentioning
confidence: 99%